2013
DOI: 10.5603/cj.2013.0026
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of aspirin plus heparin with heparin alone on asymptomatic perioperative deep vein thrombosis in candidates for elective off-pump coronary artery bypass graft: A randomized clinical trial

Abstract: Background: Symptomatic or asymptomatic deep vein thrombosis (DVT) is a common complication following coronary artery bypass graft (CABG), in which less than 1% of these patients suffer from clinically evident pulmonary embolism (PE DVT in CABG. (Cardiol J 2013; 20, 2: 139-143)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 31 publications
2
18
0
Order By: Relevance
“…The majority of the studies were observational studies (n=49), 16 studies were RCTs, and 3 were meta‐analyses (Tables 1 and 2). 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84 Of the 16 RCTs identified,1...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of the studies were observational studies (n=49), 16 studies were RCTs, and 3 were meta‐analyses (Tables 1 and 2). 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84 Of the 16 RCTs identified,1...…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies reported incidence of bleeding after cardiac surgery,17, 19, 25, 53, 54, 78, 84 but only 1 study reported risk factors for bleeding after multivariate analysis, with concurrent use of aspirin with systemic anticoagulation as the only significant risk factor in causing bleeding after valvular surgery, with some of these bleeding patients with an international normalized ratio (INR) >5 53…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It significantly reduces the bleeding risk for patients with renal insufficiency . A great deal of clinical data have displayed that the combination of antiplatelet agents and anticoagulant agents has more curative effects over antiplatelet agents alone, as well as combinations of adenosine diphosphate (ADP) inhibitor plus FXa inhibitors, aspirin plus heparin, and warfarin plus clopidogrel …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the coagulopathy induced by blood vessel damage may have adverse effect on the reoccurrence of acute coronary heart disease after recovery of blood perfusion. 3) Therefore, timely and accurate prediction of the risk of thrombosis in postoperative OPCAB patients and targeted anticoagulant therapy 4) is important to ease the hypercoagulable state of the patient and lower the incidence of adverse events. Recent studies have showed that, compared with the use of coronary artery bypass graft (CABG) surgery, the time of onset of coagulation activation and fibrinolysis phenomenon was slightly later but more durable.…”
mentioning
confidence: 99%